2010
DOI: 10.1128/iai.00507-10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pneumocystis jiroveci Humoral Immunity to Prevention of Colonization and Chronic Obstructive Pulmonary Disease in a Primate Model of HIV Infection

Abstract: Pulmonary colonization by the opportunistic pathogen Pneumocystis jiroveci is common in HIV؉ subjects and has been associated with development of chronic obstructive pulmonary disease (COPD). Host and environmental factors associated with colonization susceptibility are undefined. Using a simian-human immunodeficiency virus (SHIV) model of HIV infection, the immunologic parameters associated with natural Pneumocystis jiroveci transmission were evaluated. SHIV-infected macaques were exposed to P. jiroveci by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 64 publications
4
69
0
1
Order By: Relevance
“…We have reported evidence that Pneumocystis Kex or Kex-related antigens may play a role in protective immunity against Pneumocystis infection in a nonhuman primate model of HIV and Pneumocystis coinfection (153,154). In these studies, we found that a baseline anti-Kex plasma IgG titer of Ͼ1:12,500 in healthy macaques correlated with protection from Pneumocystis infection following SHIV immunosuppression and Pneumocystis exposure challenge (154).…”
Section: B Cellsmentioning
confidence: 74%
See 4 more Smart Citations
“…We have reported evidence that Pneumocystis Kex or Kex-related antigens may play a role in protective immunity against Pneumocystis infection in a nonhuman primate model of HIV and Pneumocystis coinfection (153,154). In these studies, we found that a baseline anti-Kex plasma IgG titer of Ͼ1:12,500 in healthy macaques correlated with protection from Pneumocystis infection following SHIV immunosuppression and Pneumocystis exposure challenge (154).…”
Section: B Cellsmentioning
confidence: 74%
“…In these studies, we found that a baseline anti-Kex plasma IgG titer of Ͼ1:12,500 in healthy macaques correlated with protection from Pneumocystis infection following SHIV immunosuppression and Pneumocystis exposure challenge (154). In contrast, monkeys with baseline titers of Ͻ1: 3200 were susceptible to Pneumocystis colonization following SHIV infection.…”
Section: B Cellsmentioning
confidence: 90%
See 3 more Smart Citations